Effectiveness and Adverse Effects of Over-the-Counter Whitening Products on Dental Tissues - de Freitas, Maiara Rodrigues; de Carvalho, Marynara Mathias; Liporoni, Priscila Christiane Suzy; Fort, Ana Clara Borges; Moura, Rodrigo de Morais e; Zanatta, Rayssa Ferreira (Frontiers in Dental Medicine, 2021)
The role of bleaching agents (e.g., hydrogen peroxide) in tooth bleaching is quite well described in literature and considered the option choice for those desiring brighter teeth, but alternative methods have emerged to fulfill the desire of patients for faster, easier, and cheaper alternatives. In this context, whitening over the counter products (OTC) are available in several vehicles, such as toothpastes, rinses, gums, paint-on varnishes, and stripes, but their effectiveness in terms of bleaching is questioned. This review aimed to describe their mode of action, whitening effectiveness, and harmful effect associate with indiscriminate use of these products. The dentifrices usually present a combination of abrasives that can induce damage to tooth surface without evidence of promoting real bleaching. The same was found for rinses, which might present low pH, with erosive potential. Charcoal have been included in the composition of these products to improve their whitening effect, but there is no evidence of that. Regarding strips, they present hydrogen peroxide in a variety of concentrations and are the only OTC product able to promote bleaching. Despite of the vehicle, the indication for the use of these products should be made after a careful individual diagnosis of the etiology of the dental staining, considering that most of them seem to be effective only in removing extrinsic stains or preventing their formation over enamel. Also, their indiscriminate use might induce damage and deleterious effects over tooth tissues or gingival tissues. The dentist should be aware of the composition and mode of action of each individual product, as they change according with the composition and the vehicle use, in order to recommend the best mode of use. Still, there is no sound evidence that any of the OTC products described promote better bleaching effect than the products indicated for professional.